Variations of Atmospheric Emissions in the Biomass Burning of Tree Species as an Environmental Indicator - Alcalá Jáuregui, Jorge Alonso; Ramírez Cubos, María Fernanda; Rojas Velázquez, Ángel Natanael; Diédhiou, Idrissa; Filippini, María Flavia; Cónsoli, Daniela; Martínez Carretero, Eduardo; Rodríguez Ortiz, Juan Carlos; Guillén Castillo, Oscar Iván; Ontivero, Marcela (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
Biomass burning (BB) serves as both an energy source and an environmental indicator. This study examined how CO₂ and fine particle emissions vary during the combustion of biomass from three tree species to determine their contribution to environmental pollution. Leave and stem samples were taken from A. farnesiana (huizache) tree, S. molle (pirul), and P. laevigata (mesquite). The dry biomass was thermally processed in a muffle furnace at temperatures ranging from 50°C to 450°C. Emissions of CO₂, particles smaller than 2.5 microns (PM2.5), particles smaller than 10 microns (PM10), and total volatile organic compounds (TVOC) were measured. The highest emission levels occurred during the pyrolysis process between 250°C and 450°C in both leaves and stems. Among the leaves, the highest emissions of PM2.5 and PM10 were found in huizache, while the highest values were found in mesquite stems. In terms of leaves, mesquite had the highest CO₂ emissions, followed by huizache and pirul. Regarding the stems, pirul had the highest atmospheric emissions of CO₂, followed by huizache and mesquite. In all cases, emission levels exceeded the limits established by Mexican and international environmental regulations, indicating a significant risk to the environment and public health. Highlights: Biomass burning (BB) is the combustion of plant materials, which are widely used for energy production This study experimentally verified the environmental impacts of biomass burning for three tree species under a laboratory pyrolysis process. The highest PM5 and PM10 emissions occurred in A. farnesiana leaves and in P. laevigata stems. The order of highest CO₂ emissions in leaves was laevigata > A. farnesiana > S. molle; in stems, it was S. molle > A. farnesiana > P. laevigata. Further comparisons across biomass burning sources and processes should strengthen evaluations of environmental impact considering air pollution.